2021
DOI: 10.1111/jpm.12739
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in life as a mediator of the associations among depression, hopelessness and suicidal ideation: A path analysis

Abstract: Accessible Summary What is known on the subject The meaning in life consists of an individual's values, experiences, goals and beliefs. It has been shown to be negatively associated with depression, hopelessness and suicidal ideation. Depression and hopelessness are related to increased suicidal ideation. Meaning in life has been shown to be a protective factor against depression, hopelessness and suicidal ideation. What the paper adds to existing knowledge A path model was developed to clarify the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…The results of the mediating effect model showed that sense of life meaning negatively predicted the level of depression. This result was consistent with a previous study on the negative correlation between sense of life meaning and depression [ 46 ]. Improving the sense of life meaning played a significant role in reducing depression.…”
Section: Discussionsupporting
confidence: 94%
“…The results of the mediating effect model showed that sense of life meaning negatively predicted the level of depression. This result was consistent with a previous study on the negative correlation between sense of life meaning and depression [ 46 ]. Improving the sense of life meaning played a significant role in reducing depression.…”
Section: Discussionsupporting
confidence: 94%
“…Perceived social support refers to the emotional experience and satisfaction of being respected, understood and supported by others in society, referring to individuals' subjective perceptions of their own social support level, their expectations and evaluations of social support, and their beliefs about their ability to receive social support (Barbara et al, 1991;Hanxiao, 2008;Ye Baojuan et al, 2014). It has been found that higher levels of perceived social support can help individuals reduce the effects of negative emotions, enhance their ability to deal with stressful events, and decrease feelings of depression (Qiu Yiwen and Yi, 2021;Sun et al, 2021). According to Stillman's hypothesis that meaning in life promotes interpersonal relationships, " there is a mutually reinforcing symbiotic relationship between the sense of social belonging and meaning in life, which means that a positive sense of social belonging will promote an individual's meaning in life, and a higher meaning in life will also promote the establishment of better interpersonal relationships (Stillman et al, 2009).…”
Section: Perceived Social Support As a Mediatormentioning
confidence: 99%
“…Numerous studies have shown that hope reduces psychological distress, maintains adaptation to disease, improves well-being, and driving directions for existence (Mattioli et al, 2008;Rustøen et al, 2011). In addition, a high level of personal hope can divert their attention from negative events (Kaleta and Justyna, 2020), reduce the risk of depression and suicide, and improve meaning in life (Sun et al, 2021). Therefore, the study tried to hypothesize the following: Hypothesis 3: Hope will act as a mediator between grit and meaning in life (grit→ hope→ meaning in life).…”
Section: The Mediating Role Of Hope Between Grit and Meaning In Lifementioning
confidence: 99%